STUDI ETNOBOTANI TUMBUHAN OBAT DALAM MASYARAKAT ADAT TIGO LUHAH TANAH SEKUDUNG SIULAK KABUPATEN KERINCI - Santosa, Tomi Apra; Arsih, Fitri; Lufri, .; Festiyed, .; Ilwandri, .; Suhaimi, . (Universitas Pakuan, 2023)
Tigo luhah tanah sekudung is an indigenous area located in the Siulak area of Kerinci Regency. The indigenous people of Tigo Luhah Tanah Sekudung have knowledge in traditional medicine. In addition, along with the development of modern medicine, the traditional medicine tradition of Tgo Luhah Tanah Sekudung indigenous people has not been inventoried. The purpose of this study was to determine the type of medicinal plants in the indigenous people of tigo luhah tanah sekudung Siulak, Kerinci Regency. Research type of exploratory descriptive research. The research was conducted in Mukai Hilir Village, Siulak Mukai District. Data collection techniques through observation, survey, questionnaire and interview. Community knowledge through questionnaires. The number of respondents in the study was 15 people. The technique of ensuring data validity is Triangulation. Data analysis is descriptive qualitative analysis. The results showed that there are 45 species and 35 families used by the indigenous people of Tigo Luhah Tanah Sekudung Siulak Kerinci Regency.